2015 GRI Index - World Bank (Washington, DC, 2015)
This 2015 index of sustainability indicators has been prepared in accordance with the internationally recognized standard for sustainability reporting Global Reporting Initiative (GRI) guidelines and complies with the ‘core option.’ The GRI Index provides an overview of sustainability considerations within the World Bank’s lending and analytical services as well as its day-to-day operations and management of staff. The World Bank aims to be comprehensive in its reporting and thus the Index includes indicators from GRIs financial sector supplement. The GRI Index covers activities from fiscal 2015, July 1, 2014, through June 30, 2015.